FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK (STUDI EMPIRIS PADA UMKM YANG TERDAFTAR DI DINAS KOPERASI DAN UMKM KABUPATEN PATI) - Heru Saputro, 09.05.52.0153; Kartika, Andi (Students Journal of Accounting and Banking, 2014)
This study aims to determine the tax paying awareness, knowledge and understanding of tax laws, a good perception of the effectiveness of tax systems, level of confidence in the Government and Legal System and the quality of service tax against the will of the different objects that SMEs. The population in this study are all registered SMEs in the department of cooperatives and SMEs starch district . Sampling was done by using the Convenience Sampling. The results of this study can be summarized as follows : awareness of the tax paying significant positive effect on the willingness to pay taxes, knowledge and understanding of tax laws is not significant positive effect on the willingness to pay taxes, a good perception of the effectiveness of the tax system over a significant positive effect on the willingness to pay taxes, level of confidence in the Government and Legal System negative effect no significant effect on the willingness to pay taxes, taxation of service quality significant negative effect on the willingness to pay taxes.Keywords: Awareness paying taxes, knowledge and understanding of tax laws, a good perception of the effectiveness of tax systems, level of confidence in the Government and the legal system and the quality of the tax service